Service oriented architecture (SOA) implementation framework for heterogeneous information systems integration - Nur Hidayat, Harun (2013)
Heterogeneous information systems (IS) creates difficulties to automatically integrate data in different IS environment. These situations have increased operating and maintenance costs as well as wasteful data storage, which is caused by data redundancy. Since the emerging of Service Oriented Architecture (SOA), the latest trend in IS development, many researchers have proposed various SOA conceptual models and frameworks. The main objective behind these efforts was to provide a guideline for a successful SOA adoption. In Malaysia, higher learning institutions have taken some initiatives to implement SOA-based systems to improve the quality of IS performance. However, most of the existing SOA frameworks available are still lacking of good design to support an integration of heterogeneous IS. In order to fill this gap, this study was conducted to seek for an opportunity to enhance the existing SOA implementation frameworks of heterogeneous IS integration. A consolidation of the existing related frameworks and consensus from experts yield a new SOA framework. A case study approach in a Malaysia public university was applied to test and validate the framework by conducted prototyping experiments with the focus on several student information systems. The evaluation from the users shows that the proposed framework has met SOA criteria like service based, data update in real time and accessibility. This finding has been proven with successful prototype experiments. With the findings and results of this study, an enhancement of SOA implementation framework was fulfilled by focusing on integrating heterogeneous IS. This is a new contribution SOA domain in the context of heterogeneous IS integration in Malaysia public universities.